Impact of Familiarity with the Accountant Professional Code of Ethics on Ethical Behavior among Students - Saiman, Nadhila Septia; Mediawati, Elis (Pancasila International Journal of Applied Social Science, 2024)
The objective of this research is to ascertain the degree to which comprehension of the professional accountant's code of ethics impacts the ethical conduct of pupils. This research employs an associative descriptive technique, using a quantitative approach. The research data was collected by administering questionnaires to three universities: Widyatama University, Padjadjaran University, and Bandung Islamic University. A total of 52 students participated in the study, and the sampling approach used was simple random sampling. SPSS 24.0 software is used for conducting hypothesis testing. The findings indicated that the comprehension of the professional accountant's code of ethics had a favorable and substantial impact on the ethical conduct of PPAK students in Bandung.